The literary imagination in Jewish antiquity - Mroczek, Eva (Oxford University Press, 2016)
The discovery of the Dead Sea Scrolls revealed a world of early Jewish writing larger than the Bible: from multiple versions of biblical texts to 'revealed' books not found in our canon. But despite this diversity, the way we read Second Temple Jewish literature remains constrained by two anachronistic categories: a theological one, 'Bible,' and a bibliographic one, 'book.' 'The Literary Imagination in Jewish Antiquity' suggests ways of thinking about how Jews understood their own literature before these categories had emerged.